Sima Marković’s National and International Dialectics - Antolović, Michael T.; Marković, Saša S. (Sociološki pregled, 2019)
Sima Marković is the most important Serbian intellectual of the communist movement in interwar Yugoslavia. Marković developed his ideological convictions through studying all key issues of social development. His attitude to economy, political and national issues derived from his aspiration to remain in line with the basics of Marxist theory while simultaneously questioning the existing knowledge related to it. In his attitudes, despite emphasizing ideological perspectives, Marković was ofen original. That satisfed his inquisitive mind but also opened up the space for doubt in the inferiority to ideological authority, but primarily to the party and leadership authority. His attitudes to nationalism in relation to the international character of the communist movement are the key topic of the work.